2015
DOI: 10.1007/s00586-015-4077-9
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of lung adenocarcinoma after total en bloc spondylectomy using frozen tumor-bearing vertebra for reconstruction

Abstract: Purpose: Total en bloc spondylectomy (TES) is a surgical procedure performed to achieve complete resection of an aggressive benign spinal tumor or a malignant spinal tumor. When reconstructing the spine after resection, we have been using liquid nitrogen-frozen resected spine bearing tumor as a bone graft, expecting an immunological response to tumor-specific antigen(s). The purpose of this article is to report a successful treatment case of lung adenocarcinoma metastasis with TES and this cryotherapy.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The benefits and reliability of frozen tumourbearing bone autograft in the limbs have been reported, with no reports of recurrence from the frozen autograft itself. [21][22][23][24][25] Moreover, there are several studies reporting its use in TES; 18,[26][27][28][29][30] however, we found that their sole application was a risk factor for IF. Liquid nitrogen-treated bone preserves proteins and enzymes in the bone and thus has excellent osteoconductive and osteoinductive abilities, 31,32 and has been shown to be effective as a bone graft in an animal model for large spinal bone defects.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The benefits and reliability of frozen tumourbearing bone autograft in the limbs have been reported, with no reports of recurrence from the frozen autograft itself. [21][22][23][24][25] Moreover, there are several studies reporting its use in TES; 18,[26][27][28][29][30] however, we found that their sole application was a risk factor for IF. Liquid nitrogen-treated bone preserves proteins and enzymes in the bone and thus has excellent osteoconductive and osteoinductive abilities, 31,32 and has been shown to be effective as a bone graft in an animal model for large spinal bone defects.…”
Section: Discussionmentioning
confidence: 64%
“…33 However, the success of the frozen autograft completely depends on the osteogenic cells from the implanted area to produce new bone. Although frozen autograft has myriad benefits, including simplicity and brevity of procedure, elimination of the need to harvest large amount of autograft, and expected stimulation of cancer immunity, [27][28][29][30] it still needs to be used in combination with an autograft. Additionally, it should be noted that robust instrumented spinal reconstruction is important along with high-quality bone grafting for successful reconstruction, since the incidence of IF after TES is still high even with autologous free vascularized grafts.…”
Section: Discussionmentioning
confidence: 99%
“…These present data show that patients with spinal metastases can live longer than estimated using currently available scores and be treated with aggressive surgical metastasectomy. With these circumstances, the clinical outcome of TES surgery has changed as we previously reported [13][14][15] . In our hospital, now we determine the indication of TES surgery or en bloc corpectomy case by case taking consideration of all factors: age, comorbidity, affected spinal level, and size of tumor, and type of cancer.…”
Section: Discussionmentioning
confidence: 95%
“…In cryotreatment, the abscopal effect has also been reported in patients with prostate and breast cancer metastasis [18,19]. Previously, three cases of spinal metastasis of carcinoma and sarcoma with regression of lung or lymph node metastasis following a total en bloc spondylectomy using tumor-bearing frozen autografts for reconstruction combined with preoperative spinal embolization have been studied in our institute [4,5,20,21]. To the best of our knowledge, previous studies have used animal models in which the antitumor immune response to cryotreatment has been assessed using immune re-challenge.…”
Section: Introductionmentioning
confidence: 96%